2015
DOI: 10.1371/journal.pone.0133666
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Eating Disturbance and Dementia Severity in Patients with Alzheimer’s Disease

Abstract: BackgroundEating is one of the most important daily activities in managing patients with dementia. Although various eating disturbance occur as dementia progresses, to our knowledge, most of the studies focused on a part of eating disturbance such as swallowing and appetite. There have been few comprehensive studies including eating habits and food preference in patients with Alzheimer’s disease (AD). The aims of this study were to investigate almost all eating disturbance and to examine the relationship of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
127
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(134 citation statements)
references
References 27 publications
2
127
0
5
Order By: Relevance
“…The present study shows that rivastigmine transdermal patch therapy increased the dietary food intake amount in AD patients experiencing loss of appetite symptomatology. Previous work has shown that a majority of AD patients experience a problematic loss of appetite . These eating problems occur even in mild AD, and represent one of the greatest sources of complications and mortality in advanced AD patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study shows that rivastigmine transdermal patch therapy increased the dietary food intake amount in AD patients experiencing loss of appetite symptomatology. Previous work has shown that a majority of AD patients experience a problematic loss of appetite . These eating problems occur even in mild AD, and represent one of the greatest sources of complications and mortality in advanced AD patients .…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, nearly 47 million people have Alzheimer's disease (AD) or a related dementia, which is the leading cause of disability in later life . More than 80% of patients with AD manifest poor food intake or loss of appetite, which might increase their risk of further cognitive impairments, neuropsychiatric symptoms and malnutrition . As a result, a vicious cycle decreases the functionality and quality of life in patients with AD.…”
Section: Introductionmentioning
confidence: 99%
“…The patients in the present study were aged ≥80 years on average, were mild‐to‐moderate AD patients with long disease duration and they had eating issues. It has been reported that loss of appetite can occur even in mild AD . Loss of appetite causes weight loss, which is associated with the onset of AD and progression of dementia .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that loss of appetite can occur even in mild AD. 19 Loss of appetite causes weight loss, which is associated with the onset of AD and progression of dementia. 20,21 Recent studies have also shown that weight loss is associated with progression from mild cognitive impairment to AD, 22 and that body mass index is significantly correlated with the amyloid beta level in the cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of the different types of dementia (e.g. Alzheimer's disease and vascular dementia) that can affect nutritional status include changes in memory, motor skills, visuospatial ability, taste, appetite and swallow function (Ikeda, Brown, Holland, Fukuhara, & Hodges, ; Kai et al., ). The presentation of the aforementioned symptoms varies among individuals as the disease progresses (van der Linde, Dening, Matthews, & Brayne, ).…”
Section: Introductionmentioning
confidence: 99%